Interferensi Metabisulfit Pada Pengukuran Kadar Sulfur Dioksida (SO2) di Udara Menggunakan Metode Tetrachloromercurat/Parasosanilin - S Sudalma; Sri Sumarni (UPT Laboratorium Terpadu, Universitas Diponegoro, 2022)
Sulfur dioxide (SO2) is an irritant gas at concentrations above 250 g/m3 which can cause respiratory problems. Sources of SO2 come from burning fuel containing sulfur. Measurement of SO2 levels in the air using the Tetrachloromercurate (TCM)/Pararosanilin method. PT